Ancient Maya commerce : multidisciplinary research at Chunchucmil - Hutson, Scott (Boulder : University Press of Colorado, 2016)
"Using a variety of evidence--archaeological, botanical, geomorpholo gical, and soil-based--contributors show how Chunchucmil, Yucatan, Mexi co was a major center for both short and long distance trade, integrati ng the Guatemalan highlands, the Gulf of Mexico, and the interior of th e northern Maya lowlands"--Provided by publisher.
Introduction / Scott R. Hutson and Bruce H. Dahlin -- Map of C hunchucmil / Scott Hutson and Aline Magnoni -- Architectural gro up typology and excavation sampling within Chunchucmil / Scott R. Hu tson, Aline Magnoni, Bruce H. Dahlin -- Chunchucmil chronology and s ite dynamics / Socorro Jimenez, Aline Magnoni, Eugenia Mansell, and Tara Bond-Freeman -- Chunchucmil's urban population / Scott R. Hu tson, Aline Magnoni, Traci Ardren, Chelsea Blackmore, and Travis Stanto n -- Environmental heterogeneity in the Chunchucmil economic region / David Hixson, Timothy Beach, Sheryl Luzzadder-Beach and Bruce H. D ahlin -- Hydrology on the edge of the Chicxulub Crater : Chunchucmil and UcÅ-Cansahcab groundwater resources / Sheryl Luzzadder-Beach an d Timothy Beach -- Hinterland settlement patterns within the Chunchu cmil economic region / David R. Hixson and Daniel E. Mazeau -- So ils and agricultural carrying capacity / Timothy Beach, Sheryl Luzza dder-Beach, Ryan V. Sweetwood, Patrice Farrell, Daniel E. Mazeau, and R ichard E. Terry -- Perishable resources produced for exchange in the Chunchucmil economic region / Bruce H. Dahlin, Traci Ardren, David R. Hixson, and Anthony P. Andrews -- Marketing within Chunchucmil / Scott R. Hutson, Richard E. Terry, and Bruce H. Dahlin -- Connec tions beyond Chunchucmil / Traci Ardren, Scott R. Hutson, David R. H ixson and Justin Lowry -- Conclusion / Scott R. Hutson.
Includes bibliographical references and index.
Keywords: Mayas -- Commerce; Mayas -- Economic conditions; Mayas -- Antiquities; Excavations (Archaeology) -- Mexico -- Chunchucmil Site; Mexico -- Antiquities; Chunchucmil Site (Mexico)